(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The increasing demand for miniaturization and high-precision fabrication in electronic materials, including semiconductors, MEMS, and microelectronics packaging, necessitates advanced micromachining techniques capable of producing microscale features with minimal thermal damage. This study presents the design and analysis of ultrafast pulsed laser systems tailored for precision micromachining applications in such materials. Theoretical modeling encompassed ablation threshold calculations, thermal diffusion analysis, and spot size-fluence optimization, revealing that femtosecond pulses (\ 300 fs) enable cold ablation with negligible heat-affected zones due to their ultrashort energy deposition timescales. An experimental setup was developed using a femtosecond laser (1030 nm, 300 fs) integrated with galvanometric scanners and precision stages, processing silicon wafers, glass substrates, and thin metal films. Machining parameters, including pulse energy (5–150 µJ), repetition rate (100–500 kHz), and scanning speed (0.1–10 mm/s), were systematically varied. Results demonstrated high-quality micromachining outcomes, achieving minimum feature sizes of \ 1.5 µm, smooth surfaces with RMS roughness of 20–50 nm, and minimal redeposition or tapering. Pulse characterization via autocorrelation and FROG confirmed clean temporal profiles, while system stability tests showed <±2% energy fluctuation, ensuring consistent ablation performance. The findings confirmed theoretical predictions, with negligible thermal damage across all materials processed. Comparison with previous studies highlighted comparable or superior machining quality, validating the proposed design framework. Challenges encountered included beam delivery alignment sensitivity and minor pulse energy fluctuations, emphasizing the need for routine calibration and active stabilization for industrial applications. This research contributes by establishing an integrated design, modeling, and experimental validation framework for ultrafast laser micromachining systems, paving the way for their effective deployment in electronic manufacturing. Future work will focus on multi-material processing optimization, AI integration for adaptive real-time machining, and energy efficiency improvements to enable high-throughput, scalable, and sustainable ultrafast laser-based fabrication solutions.